PENGARUH KUALITAS PELAYANAN PUBLIK DAN DISIPLIN KERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT: (Studi Pelayanan Haji Di Kantor Kementerian Agama Kabupaten Kaur) - Budiman; Sakti, Budiman; Rahimandani; Elza Risanti (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2025)
This study aims to analyze the influence of public service quality and employee work discipline on public satisfaction with Hajj services at the Ministry of Religion, Kaur Regency. The research employed a quantitative approach using a sample of 50 respondents from the community who registered as prospective Hajj pilgrims. Three research problems and hypotheses were tested through partial (t-test) and simultaneous (F-test) analyses. To determine the magnitude of the effect of each independent variable-public service quality and employee discipline-on public satisfaction, multiple linear regression analysis was applied. The results based on respondents’ assessments indicated that the quality of public services was categorized as “very good,” employee work discipline as “good,” and overall satisfaction with Hajj services as “good.” The hypothesis testing results show that public service quality (t = 4.320, p < 0.05) and employee work discipline (t = 8.946, p < 0.05) both have a positive and significant effect on public satisfaction. Simultaneous testing also revealed a significant influence of both variables (F = 73.621, p < 0.05). These findings conclude that improving public service quality and strengthening employee discipline significantly enhance community satisfaction with Hajj services at the Ministry of Religion, Kaur Regency.